Tensile properties analysis and characterization of single fiber and biocomposites - Hassan, Mohamad Zaki; Ibrahim, Mohamad Ikhwan; Sapuan, S. M. (CRC Press, 2022)
The natural fiber is an emerging area in polymer science and the best option for replacing synthetic polymer in relevant applications. The study reviewed the future development of tensile strength and stiffness properties of monotonic single fiber and biocomposite using Weibull analysis. The Weibull distribution model that statistically interprets the reliability of distribution of tensile test was deeply discussed. The distinctive parameters, especially in determining the Weibull modulus (m), were also examined. Further, the latest trend in evaluating the single fiber and biocomposite structures by using a statistical approach was addressed.